Efeitos da adubação nitrogenada na cultura do milho sob estresse salino em dois solos - Braz, Régis dos Santos (2018)
The increase of nitrogen fertilization as a mitigation of the deleterious effects of salinity has been described for several crops. However, the reduction in plant growth, caused by saline stress, can result in lower nutrient uptake, causing the loss of these nutrients by leaching, such as nitrogen. This loss, even in saline conditions, is also dependent on the textural properties of the soil. The objective of this study was to evaluate the effects of nitrogen fertilization on maize plants submitted to saline stress in two soils. The work was done in a greenhouse, using soil columns (100 x 20 cm). The experimental design was a completely randomized design, with four replications, in a 2 x 2 x 4 factorial scheme, corresponding to two soils (Ultisol and Neosol), two nitrogen rates (105 and 210 kg ha-1 N) and four salinity levels of irrigation water(0,5; 2,0; 4,0 and 6,0 dS m-1). Plant growth, total chlorophyll, leaf gas exchange, leaf content of organic and inorganic solutes, nitrogen use efficiency and soil chemical attributes were evaluated. Salinity reduced plant growth, leaf gas exchange, total chlorophyll content and promoted leaf accumulation of proline, N-aminosoluble and carbohydrates. Although it showed interaction with the soil type, nitrogen did not generally attenuate the effects of salinity on the aforementioned parameters. Salinity also decreased leaf contents of Ca, Mg, and N. However, it increased Na, Zn, Cu, Mn, Fe and Cl levels, with the highest increases occurring in the plants grown in Ultisol with the highest nitrogen rate. The efficiency of nitrogen use was higher when the lowest nitrogen rate was used. However, it did not show interaction with salinity, which promoted reduction of A/N-rate and A/N-leaf with increase in saline levels. Evaluating the chemical attributes of the soils, it was verified that EC and Na content increased, while pH decreased as a result of salinity. However, these responses were dependent on soil type, it was the Ultisol which promoted higher EC, Na and higher pH reduction. The highest Mg and K contents were also found in the Ultisol, but not related to the salinity or nitrogen rates. On the other hand, the Ca content in the soil increased in the Ultisol and with the increase of the saline levels. The salinity increased NO3- and N-total in the soil, with greater increase of NO3- in the Ultisol fertilized with the rate of 210 kg ha-1 of N.